Optimalisasi Calon Induk Ikan Bersertifikat sebagai Upaya Peningkatan Produktivitas Kelompok Pembudidaya Ikan Rizky Mina Utama Kota Tarakan - Gloria Ika Satriani; Ery Gusman; Ira Maya Abdiani; Diana Purnama Sari; Awaludin Awaludin (Jurnal PKM Manajemen Bisnis, 2026)
The availability of high-quality, certified broodstock is a key factor in improving fish farming productivity. However, many small-scale fish farmer groups still rely on uncertified broodstock, leading to reduced fry quality and lower production yields. In response to this issue, a community service program titled Optimization of Certified Broodstock as an Effort to Increase the Productivity of the Rizky Mina Utama Fish Farmers Group in Tarakan City was conducted. The program aimed to enhance the knowledge and technical skills of local fish farmers regarding the selection and management of certified broodstock to improve aquaculture outcomes. The activity was implemented in July 2025 at the Rizky Mina Utama Fish Farmers Group (POKDAKAN) in Karang Harapan Subdistrict, Tarakan City. The implementation team consisted of 25 lecturers and students from Borneo Tarakan University, while the participants included 15 members of the Rizky Mina Utama fish farmers group. The methods used in the program included presentations, hands-on practical training, interactive discussions, and Q&A sessions. The results showed a significant increase in participants’ understanding of broodstock certification, selection techniques, and proper broodstock management. Moreover, the program fostered greater awareness of the importance of using certified broodstock to ensure fry quality and production sustainability. This initiative is expected to support long-term improvements in local aquaculture practices.